Pregunta
2. 5implify and write in the rectangular form 21) \( 60 j^{8}+10 j^{4}-20 j^{20} \)
Ask by Vaughn Franklin. in South Africa
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
The simplified rectangular form of the expression is \( 50 \).
Solución
To simplify the expression and write it in rectangular form, let's analyze each term involving the imaginary unit \( j \):
\[ 60j^{8} + 10j^{4} - 20j^{20} \]
Since \( j \) is the imaginary unit, it has the property that \( j^4 = 1 \). Therefore, any exponent of \( j \) can be reduced by taking it modulo 4.
1. **Simplify each term:**
- \( j^8 = (j^4)^2 = 1^2 = 1 \)
- \( j^4 = 1 \)
- \( j^{20} = (j^4)^5 = 1^5 = 1 \)
2. **Substitute the simplified values back into the expression:**
\[
60j^{8} + 10j^{4} - 20j^{20} = 60(1) + 10(1) - 20(1) = 60 + 10 - 20 = 50
\]
3. **Express in rectangular form:**
The result is a real number with no imaginary part, so the rectangular form is simply:
\[
50 + 0j
\]
However, it's common to present just the real part when the imaginary part is zero.
**Final Answer:**
\[ 50 \]
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Mind Expander
To simplify the expression \( 60 j^{8} + 10 j^{4} - 20 j^{20} \), we can use the property that \( j^2 = -1 \). Let's break it down: - \( j^4 = (j^2)^2 = (-1)^2 = 1 \) - \( j^8 = (j^4)^2 = 1^2 = 1 \) - \( j^{20} = (j^{2})^{10} = (-1)^{10} = 1 \) Substituting these values back into the expression: \[ 60(1) + 10(1) - 20(1) = 60 + 10 - 20 = 50 \] So, the expression simplifies to \( 50 \). In rectangular form, it is simply \( 50 + 0j \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium